Applied psychology for project managers : (Springer, 2015)
This book offers an essential manual for project managers, project management offices (PMO?s), trainers and consultants, addressing the psychological side of project management. Written by leading scholars in organizational psychology and by top experts in project management, it covers all major psychological topics that are key to project success. The book features dedicated chapters on leadership and teamwork, including virtual and intercultural cooperation, commitment, and motivation of project teams. It adds a psychological perspective to personnel management, decision-making, information and knowledge management, and communication in project work. Power, influencing tactics and other aspects of stakeholder management are covered, as well as project coaching, innovation and creativity, self-management, and the management of conflicts, risks and crises.